Is Soccer Good for You? The Motivational Impact of Big Sporting Events on the Unemployed - Philipp Doerrenberg; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2014)
We examine the effect of salient international soccer tournaments on the motivation of unemployed individuals to search for employment using the German Socio Economic Panel 1984-2010. Exploiting the random scheduling of survey interviews, we find significant effects on motivational variables such as the intention to work or the reservation wage. Furthermore, the sporting events increase perceived health as well as worries about the general economic situation.
Keywords: D8; J2; J6; 330; sporting events; soccer; unemployment; well-being